Design and fabrication of road dust cleaning machine / Ahmad Safwan Ariffin - Ariffin, Ahmad Safwan (2022)
Cleaning is the main basic need for all human beings and it is necessary for daily routine process. The conventional road and floor cleaning machine is most widely used in many applications such as roads, railway stations, airports, hospitals, bus stands, buildings, and colleges. In recent years, most people prefer to commute by train or bus, and as a result, these areas are littered with biscuit wrappers, cold drink bottles, and other items. It is a user friendly as well as eco-friendly. In this project are to design and develop road cleaning machine capable of cleaning some part of road as well as around space .This target also to fabricate a machine that able to help people to do their cleaning at wide outdoor area. This project goes through many phases and aspect to fill the customers need based on recommendation and survey from every layer of life. All the finding are then turn into ideas to finalize the design and model for this project